Investigation of the First Case of Monkeypox in Chaiyaphum Province, from August 21 to September 11, 2023 - Hanbungkla, Sabaitong; Kaomuanghmoo, Chinnawat (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
On August 21, 2023, the Province Public Health Office, Chaiyaphum received notification of a confirmed case of monkeypox (mpox) from Pattaya, Chonburi Province. The individual in question had a history of sexual contact with an unknown man. An investigation was conducted to confirm the diagnosis, describe the epidemiological characteristics of the case, identify risk factors, determine the transmission source, examine infection among the case's contacts, and recommend appropriate preventive and control measures. The descriptive study involved reviewing the patient’s medical records from the hospital and case reports, interviewing the patient, close family contacts, physicians, and health personnel involved in the patient’s care. Samples were collected from the patient to detect the mpox virus using real-time PCR and to identify viral strain through genome sequencing. An environmental study was also conducted, and the mpox surveillance system in Thepsathit district was assessed. The results identified one confirmed case of mpox in a 33-year-old Thai male with HIV infection, who identifies as gay (LGBTQ). He had traveled by bus from Pattaya, Chonburi province, and experienced symptoms such as fever, muscle pain, pain and swelling in the inguinal lymph nodes, and developed rashes and papules that first appeared on perineum on August 14, 2023, and before spreading across his body. Samples from the lesion roof of a pustule on the penis tested positive for the mpox virus in two laboratories, with the viral strain identified as West Africa cade IIa. All four high-risk, six low-risk and twelve no-risk contacts of this case tested negative for mpox infection. Although he was an imported case, there was no evidence of transmission to others or futher spread in Chaiyaphum province. The mpox surveillance system in Thepsathit district was improved. The identified risk factor for mpox virus infection was direct contact through sexual activity with infectious skin or other lesions, such as those in the mouth or on the genitals. The individual had changed sexual partners through a dating application for the gay community. Therefore, we recommended that hospitals include emerging infectious diseases in their surveillance system to timely update the situation. This can be achieved by designed a surveillance report for suspected cases of mpox for patian care wards, clinics, and pharmacies, and by adding risk communication channels in sexually transmitted disease clinics and LGBTQ groups.